On the genus Megabahita Linnavuori & DeLong, 1978 (Hemiptera: Cicadellidae): new species, redescriptions, key to species, and a synonymy - Camisão, Beatriz M.; Zahniser, James N.; Takiya, Daniela M. (Zootaxa, 2025)
The Neotropical genus Megabahita is reviewed and redescribed. A new species from Minas Gerais, Brazil, is described and illustrated. Megabahita cipoensis sp. nov. can be distinguished by the male pygofer without dorsal processes and with ventral processes spatulate, and the aedeagus with atrium relatively robust and without apical processes. Megabahita gigantea Linnavuori & DeLong, 1978 is redescribed and illustrated. Megabahita stylata DeLong, 1984 is considered a junior synonym of Sanestebania rotundiceps Linnavuori & DeLong, 1978, syn. nov. Megabahita patula DeLong, 1982 is transferred to Frequenamia, making the new combination Frequenamia patula (DeLong) comb. nov. A taxonomic key to species of Megabahita is provided for the first time.